Development of Website-Based Learning Media on Reaction Rate Material to Improve Student Learning Outcomes - Evita Harti Nanda; Rudiana Agustini (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This development research aims to describe the feasibility of website-based learning media for reaction-rate material. The feasibility of learning media is reviewed in terms of validity, practicality, and effectiveness. Media validity is measured by content validity and construct validity. The practicality of the media is measured by student responses and activities. Effectiveness is measured by the percentage of classical completeness and the improvement of students' learning outcomes. The research method used in this research is Borg and Gall's Research and Development (R&D) method, which has been modified by Sukmadinata. Media trials were conducted at SMA Negeri 20 Surabaya on 33 students of class XI MIPA 2 who had previously received reaction rate material. This website-based learning medium is declared feasible. The results of content and construct validity show valid results in each aspect with a mode between 4 and 5. Practicality results show that web-based learning media is practical with 98,10% of relevant student activities at the first meeting and 99,05% at the second meeting, while the percentage acquisition of each aspect in the student response gets a percentage of  90%. The results of the effectiveness of learning media obtained classical completeness results of 87.9% and an N-Gain score of 0.78. This is supported by the results of the Paired sample t-test of 0.000, which means there is a significant average difference in learning outcomes.